Ḥuqūq al-insān wa al-dīmūqrātīyah wa dawr al-mujtama‘ al-madanī bi Indūnīsīyā - Yakin, Ayang Utriza (Studia Islamika, 2014)
This article discusses the issue of human rights and its relation to democracy. The paper attempts to elaborate on the concepts and principles of democracy that are an absolute prerequisite for the respect of human rights in Indonesia. Without there being an established democracy in the country, then, certainly, respect for and enforcement of human rights would never have materialized. The article will also explain the democratization movement in Indonesia and the role of civil society, including actors such as non-government organizations (NGOs), the mass media/press and religious organizations, in the enforcement of human rights and democracy. This paper hopes to provide a thorough contribution to the understanding and recognition of democratic principles and of democracy, itself, in making available space for the respect of and enforcement of human rights, including through the role of civil society.DOI: 10.15408/sdi.v21i2.1042